1999
DOI: 10.1074/jbc.274.53.37731
|View full text |Cite
|
Sign up to set email alerts
|

Channel Formation by FhaC, the Outer Membrane Protein Involved in the Secretion of the Bordetella pertussis Filamentous Hemagglutinin

Abstract: Many virulence factors of pathogenic microorganisms are presented at the cell surface. However, protein secretion across the outer membrane of Gram-negative bacteria remains poorly understood. Here we used the extremely efficient secretion of the Bordetella pertussis filamentous hemagglutinin (FHA) to decipher this process. FHA secretion requires a single specific accessory protein, FhaC, the prototype of a family of proteins necessary for the extracellular localization of various virulence proteins in Gram-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
81
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 38 publications
7
81
0
1
Order By: Relevance
“…However, previous studies performed with bacterial Omp85-like proteins have not supported this notion. Although several bacterial family members have been demonstrated to have pore activity, none had been found to be multimeric (7,15,16). Immunoblot analysis revealed that N. meningitidis Omp85 exists in a high-molecular weight complex (7); however, earlier work by Manning et al demonstrated that this protein interacts with several heterologous proteins in the OM (44), thus precluding any conclusion regarding the structural organization of N. meningitidis Omp85.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…However, previous studies performed with bacterial Omp85-like proteins have not supported this notion. Although several bacterial family members have been demonstrated to have pore activity, none had been found to be multimeric (7,15,16). Immunoblot analysis revealed that N. meningitidis Omp85 exists in a high-molecular weight complex (7); however, earlier work by Manning et al demonstrated that this protein interacts with several heterologous proteins in the OM (44), thus precluding any conclusion regarding the structural organization of N. meningitidis Omp85.…”
Section: Discussionmentioning
confidence: 85%
“…In bacteria, the only two family members that have been studied in detail are ShlB and FhaC, both of which have been demonstrated to have pore activity. However, no convincing evidence for multimer formation has been obtained for either ShlB or FhaC, thus contrasting with eukaryotic Omp85-like proteins (15,16). These findings have led others to suggest that the tetrameric Omp85 protein translocation system in eukaryotes may have evolved from more primitive, monomeric bacterial Omp85 homologs (3,5).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…PTBs of recent interest are, e.g. outer membrane proteins (which secrete adhesins such as hemagglutinin) (8,9) and bacterial (1, 7, 10 -12), mitochondrial (Tob55/Sam50) (5,13,14), and chloroplast outer membrane proteins (Toc75) (15) of the Omp85 family. The PTBs are partitioned into two functional categories, namely in translocation of precursor proteins across the membrane and in the assembly of outer membrane proteins (3).…”
mentioning
confidence: 99%